DEVELOPMENT AND VALIDATION OF KETOROLAC TROMETHAMINE ANALYSIS METHODS USING HPLC AND TEST ITS STABILITY - Raihanah; Supriyadi (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2024)
Determination of ketorolac tromethamine levels based on United States Pharmacopeia (USP) using L7 column 4.6 mm x 25 cm; 5 μm with mobile phase tetrahydrofuran and buffer (30:70). Tetrahydrofuran has oxidative properties and has a high UV limit and the presence of peroxide impurities in it can affect the stability of the analyte so that the use of tetrahydrofuran is often avoided. Therefore, a method for analyzing ketorolac tromethamine was developed by applying of High Performance Liquid Chromatography (HPLC) using C18 column with acetate buffer pH 4.2 and methanol (20:80) as mobile phase, flow rate 1.0 mL/minute, wavelength 318 nm, and 10 μL injection volume. The validation results obtained a linearity value (r) 0.9982, value of LOD is 9.61 μg/mL and LOQ is 29.11 μg/mL. The results of precision test obtained %RSD equal to 0.776% and the accuracy test of the sample concentrations 80%, 100% and 120% show the %recovery are 94,79%, 99,42% and 92,83%, respectively. New degradants were formed with acid exposure of 80.66%, base exposure of 59.30%, temperature exposure (70-90°C for 3 hours) are 1.28%, 15.06%, and 18.40 %, respectively. Oxidation exposure (H2O2 1%, 3% and 5%) are 11.36%, 13.98% and 14.79%, respectively. All the research results can be concluded that the method development and validation results can be used for the analysis of ketorolac tromethamine and testing its stability.